2019
DOI: 10.1016/j.heliyon.2019.e02979
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge-based products and economic complexity in developing countries

Abstract: Economic growth and development requires greater access to global markets, while developing countries face many challenges in terms of trade liberalization. That is why most of the countries relying on natural income sources have not been able to improve their indicators of economic complexity and high technology utilization. The purpose of this study was to investigate the impact of trade liberalization on the economic complexity as a strategy adopted by the Middle East developing economies during the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Gnangnon (2018) has found that higher AfT ows for trade policy and regulation are associated with greater trade policy liberalization. As trade policy liberalization can also lead to greater economic complexity (e.g., Sepehrdoust et al 2019 -see also the discussion below concerning the effect of trade openness on economic complexity), it could ensue that an increase in AfT ows would promote economic complexity.…”
Section: Effect Of Aft Ows On Economic Complexitymentioning
confidence: 99%
See 4 more Smart Citations
“…Gnangnon (2018) has found that higher AfT ows for trade policy and regulation are associated with greater trade policy liberalization. As trade policy liberalization can also lead to greater economic complexity (e.g., Sepehrdoust et al 2019 -see also the discussion below concerning the effect of trade openness on economic complexity), it could ensue that an increase in AfT ows would promote economic complexity.…”
Section: Effect Of Aft Ows On Economic Complexitymentioning
confidence: 99%
“…In contrast with the voluminous work on the macroeconomic determinants of export product diversi cation, few studies have investigated the macroeconomic determinants of economic complexity (e.g., Chu, 2020;Hausmann and Hidalgo, 2014;Lapatinas, 2019;Lapatinas and Litina, 2019;Sepehrdoust et al, 2019). The baseline model speci cation presented below draws from these studies, and includes, apart from our main variables of interest -namely the indicators of productive capacities (i.e, overall productive capacities and its components) as well as total AfT ows -, a set of control variables that are deemed to in uence the effect of these key variables of interest on economic complexity.…”
Section: Model Speci Cationmentioning
confidence: 99%
See 3 more Smart Citations